Barriers and challenges faced by women with congenital bleeding disorders in Europe: Results of a patient survey conducted by the European Haemophilia Consortium. Issue 3 (29th April 2019) - Noone, Declan; Skouw‐Rasmussen, Naja; Lavin, Michelle; van Galen, Karin P. M.; Kadir, Rezan A.
Abstract : Introduction: Historically, issues faced by women with bleeding disorders (WBD) have been underestimated. While advances in genetic testing have resulted in improvements, significant challenges remain in the initial recognition of abnormal bleeding and referral of WBD. Methods: The European Haemophilia Consortium (EHC) developed a questionnaire for WBD to provide insights into the barriers and challenges faced by WBD in Europe. Results: In total, 709 WBD responded to the survey from 32 countries, predominantly from western European countries (94%). A delay in ascertaining the diagnosis of a congenital bleeding disorders (CBD) remains, with a median age at diagnosis of 16 years. The presence of family history is strongly associated with a lower median age at diagnosis of 6 years. WBD reported significant disease impact on their day‐to‐day life, most evident for the rarer CBD. The bleeding symptom of biggest impact on daily life is heavy menstrual bleeding (HMB), reported by 55% of women. Importantly, 25% of WBD reports that their condition severely impacted their decision to have or has prevented them from having children. Respondents registered with Haemophilia Treatment Centres (HTC) are 2.2 times more likely to receive treatment compared to WBD in other hospital services. Conclusion: Improved education for both patients and healthcare providers is essential to improve time to diagnosis, access to treatment and psychosocial supports for WBD in Europe.